Model-based roentgen stereophotogrammetric analysis using elementary geometrical shape models: Reliability of migration measurements for an anatomically shaped femoral stem component - Xu, Jing; Cao, Han; Sesselmann, Stefan; Taylor, Dominic; Forst, Raimund; Seehaus, Frank (Applied Sciences, 2020)
Elementary Geometrical Shape (EGS) models present an alternative approach to detect in vivo migration of total hip arthroplasty using model-based Roentgen Stereophotogrammetric Analysis (mbRSA). However, its applicability for an irregular-shaped femoral stem and the reliability of this mbRSA approach has not been proven so far. The aim of this study is to assess the effect of multi-rater and an anatomically shaped femoral stem design onto resulting implant to bone migration results. The retrospective analysis included 18 clinical cases of anatomically shaped stem with 10-year RSA follow-ups. Three raters repeatedly measured all RSA follow-ups for evaluating the rater equivalence and intra-rater reliability. The results proved the equivalence between different raters for mbRSA using EGS models (mbRSA-EGS), hence it simplified the investigation of rater reliability to intra-rater reliability. In all in-plane migration measurements, mbRSA-EGS shows good intra-rater reliability and small intra-rater variability (translation: <0.15 mm; rotation: <0.18 deg). However, the reliability is worse in the out-of-plane measurements, especially the cranial-caudal rotation (intra-rater variability: 0.99–1.81 deg). Overall, mbRSA-EGS can be an alternative approach next to surface models while the in-plane migration of femoral stem (e.g. the implant subsidence for loosening prediction) have more research interested than other directions.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Accuracy; Elementary geometrical shape models; Hip arthroplasty; Migration; Model-based RSA; Reliability